Adaptasi Alat Ukur Team learning capability (TLC) Pada Karyawan Generasi Z - Komalasari, Shanty; Handoyo, Seger; Herachwati, Nuri (Jurnal Studia Insania, 2023)
This research discusses the "Adaptation of Team learning capability (TLC) Measurement Tool in Generation Z." Team Learning, or team-based learning, refers to the capacity of organizational members to avoid making personal assumptions and to think freely together as one organization. Group research entails dialogue among organizational members and the presence of customs that allow them to express their thoughts freely and openly for the benefit of the organization. The measurement tool used in this study is the result of the adaptation of the Team learning capability (TLC) measurement tool by Batt-Rawden et al. (2018). The method used is qualitative, with the technique of distributing questionnaires through Google Forms. There are several criteria for respondents in this study, namely those born between 1995 and 2010, currently or previously employed, and willing to participate as respondents. One hundred four (104) respondents filled out the questionnaire through Google Forms, and most respondents were born between 1999 and 2003. This research is expected to provide information on the adaptation of the measurement tool for Generation Z using the Team learning capability (TLC) measurement tool by Batt-Rawden et al. (2018). Keywords: Adaptation Measurment Instrument, Generation Z Employees, Team Learning Capability